CLINICAL AND DIAGNOSTIC ASPECTS OF VERTEBROBASILAR INSUFFICIENCY IN THE ELDERLY AGE - Djurabekova Aziza Taxirovna; Khasanov Shamshod; Utaganova Guljahon Xolmuminovna (International Engineering Journal For Research & Development, 2021)
The great attention of specialists to the problem of vertebrobasilar insufficiency is dictated by the high prevalence, complexity of pathogenesis and the difficulty of stabilizing the therapeutic approach (2,4,13). To date, the cause of acute disorders of cerebral circulation, and in some cases with a fatal outcome, is a violation of blood flow in the basin of the vertebrobasilar system, according to various authors, about 30-40% of all cases of cerebral accidents (5,8,11). Accordingly, the issue of early diagnosis, optimization of the last therapy and preventive measures of vertebrobasilar insufficiency is a priority and urgent one. The vertebrobasilar system is quite complex in its mechanism, the manifestation of clinical signs is quite diverse, it can be disguised as various diseases of ENT pathology (Miniere's disease), cervical sciatica, cervical myelitis sirito, volumetric formation of the posterior cranial fossa, etc